A physiological characterization in controlled bioreactors reveals a novel survival strategy for Debaryomyces hansenii at high salinity. Issue 5 (6th January 2021) - Navarrete, Clara; Frost, August T.; Ramos‐Moreno, Laura; Krum, Mette R.; Martínez, José L.
Abstract: Debaryomyces hansenii is traditionally described as a halotolerant non‐conventional yeast and has served as a model organism for the study of osmotolerance and salt tolerance mechanisms in eukaryotic systems for the past 30 years. However, unraveling of D. hansenii 's biotechnological potential has always been difficult due to the persistent limitations in the availability of efficient molecular tools described for this yeast. Additionally, there is a lack of consensus and contradictory information along the recent years that limits a comprehensive understanding of its central carbon metabolism, mainly due to a lack of physiological studies in controlled and monitored environments. Moreover, there is little consistency in the culture conditions (media composition, temperature, and pH among others) used by different groups, which makes it complicated when trying to get prevalent conclusions on behavioral patterns. In this work, we present for the first time a characterization of D. hansenii in batch cultivations using highly controlled lab‐scale bioreactors. Our findings contribute to a more complete picture of the central carbon metabolism and the external pH influence on the yeast's ability to tolerate high Na + and K + concentrations, pointing to a differential effect of both salts, as well as a positive effect in cell performance when low environmental pH values are combined with a high sodium concentration in the media. Finally, a novel survival strategy at very high salinity (2 M) is proposed for this yeast, as well as potential outcomes for its use in industrial biotechnology applications. Take Away: High salt concentrations stimulate respiration in Debaryomyces hansenii . Sodium exerts a stronger positive impact on cell performance than potassium. μ max is higher at a combination of low pH, high salt, and high temperature. Concentrations of 2 M salt result in slower growth but increased biomass yield. The positive effect of salts is enhanced at low glucose concentration. Abstract : A controlled batch cultivation of the "salt‐loving" yeast Debaryomyces hansenii in a highly instrumented lab‐scale bioreactor, at the DTU Fermentation core lab (Technical University of Denmark).